2017
DOI: 10.1088/2053-1591/aa8042
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide film based highly responsive infrared detector

Abstract: Due to the unique optical properties, graphene can effectively be used for the detection of infrared light. In this regard, reduced graphene oxide (RGO) has drawn considerable attention in scientific society because of simplicity of preparation and tunable properties. Here, we report the synthesis of RGO by solvothermal reduction of graphene oxide (GO) in ethanol and the detection of infrared light (1064 and 1550 nm) with metal-RGO-metal configuration. We have observed that photocurrent, responsivity as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…β depends on complex processes of exciton generation, trapping, and recombination , Kind et al, 2002. β is 0.89, 0.99, 0.85 and 0.97 for 1550, 1064, 632 and 325 nm wavelength respectively.…”
Section: = *mentioning
confidence: 99%
See 2 more Smart Citations
“…β depends on complex processes of exciton generation, trapping, and recombination , Kind et al, 2002. β is 0.89, 0.99, 0.85 and 0.97 for 1550, 1064, 632 and 325 nm wavelength respectively.…”
Section: = *mentioning
confidence: 99%
“…where h is Plank constant 6.626 × 10 -34 J.s., C is light speed 3×10 8 m.s -1 , q is electronic charge (1.6×10 -19 coulomb) and λ is the wavelength of incident radiation (Khan et al, 2017b, Xia et al, 2009, Afzali et al, 2014. Responsivity and EQE of the device with other reported data at different incident electromagnetic radiation have been listed in table 1.…”
Section: = *mentioning
confidence: 99%
See 1 more Smart Citation
“…From the last few decades, substantial research is being done in the field of photodetectors which has led to immense improvements in their performance such as very high responsivities, ultrafast response, and photodetection in a broad range of wavelengths. Therefore, photodetectors find their applications in a wide variety of fields ranging from day-to-day consumer electronics to more advanced and complex applications, such as industrial and environmental monitoring, flame detection, space communication systems, optical communication, missile technology, proximity sensors, and so forth. , Typically, these photodetectors require an externally applied bias as the driving force for efficient separation of the photogenerated electron–hole pairs. ,, Consequently, for systems containing a large number of sensors, energy supply becomes one of the major challenges in the current energy scenario. In regard to the global energy crisis, lots of efforts are being made in the fields of photovoltaics, supercapacitors, thermoelectrics, and self-powered nanodevices. Self-powered photodetectors, which generate a self-sufficient potential for effective separation of the photogenerated charge carriers, have recently attracted considerable attention because of their numerous advantages. …”
Section: Introductionmentioning
confidence: 99%
“…The reduction of graphene oxide (GO) restores the sp 2 carbon network facilitating controllable bandgap and conducting pathways through C/O ratio manipulation where hybridizations between p-orbitals of oxygen atoms and the frontier orbital of carbon atoms determines the bandgap of rGO. This restoration of sp 2 carbon network in rGO is associated with fast carrier dynamics and enhanced Visible-NIR absorption through conducting π-conjugated carbon network and structural defect driven disordered mid-band states [14,16]. Boukhvalov et al have shown a variation in bandgap of GO sheets from 2.8 to 1.8 eV with varying oxygen containing groups (-OH, COOH, C-O, C=O) coverage (75%-50%) on graphene sheets [17].…”
Section: Introductionmentioning
confidence: 99%